A high-reliability medium-voltage fire-resistant power cable and a matching comprehensive fire-resistant structure, a heat-insulating layer formula and a preparation method
Patent Information
- Application Number
- CN202611326698.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-30
- Publication Date
- 2026-10-16
AI Technical Summary
克服现有耐火电缆单层结构隔热差、陶瓷壳开裂、发泡层开孔导热及耐火时长<180min的缺陷,提供三区阶梯耐火复合结构、高氧指数真空闭孔配方及配套密闭挤塑负压定型工艺,大幅提升中压电缆长时耐火可靠性
(1)三区阶梯隔热,传热路径倍增,耐火时长稳定180min,通过950℃试验;
Smart Images

Figure CN122930641A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medium-voltage fire-resistant power cable manufacturing technology, specifically involving a high-reliability medium-voltage fire-resistant power cable and its supporting integrated fire-resistant structure, insulation layer formula and preparation method, including a stepped integrated fire-resistant and heat-insulating composite structure, a special foaming formula and an integrated extrusion process. Background Technology
[0002] Medium-voltage fire-resistant cables are widely used in critical locations such as fire protection, rail transit, hospitals, and data centers, where power supply must be maintained for at least 90 minutes during a fire, with high-end applications requiring 180 minutes. Existing fire-resistant cables are mostly single-layer mica tape wrapped or single-layer ceramic extruded, with the following main drawbacks: (1) Single-layer mica tape is prone to pulverization and detachment at high temperatures, resulting in a short heat insulation path and rapid heat conduction to the cable core, making it difficult to meet the 180-minute long-term fire resistance requirement. For example, Chinese patent CN221946844U discloses a high flame-retardant and fire-resistant variable frequency cable, whose fire-resistant layer uses two layers of calcined mica wrapped in an overlapping manner. Although it claims to be able to withstand 950℃ and 180 minutes of fire resistance, this solution still falls within the category of single-layer mica tape structure and does not solve the inherent defects of mica pulverization and detachment at high temperatures and the short heat insulation path. The single-layer ceramicized layer shrinks and cracks at high temperatures, allowing oxygen / heat radiation to penetrate, resulting in oxygen and heat insulation failure.
[0003] (2) Conventional flame-retardant insulation layers are solid structures with high thermal conductivity and lack long-term heat absorption and storage mechanisms. The water vapor generated by the dehydration of hydroxides dissipates quickly, resulting in poor continuous cooling effect.
[0004] (3) Ordinary foam insulation layers are mostly open-cell structures, and air convection intensifies heat conduction; and there is no matching closed extrusion and negative pressure shaping process, so the cells are easy to connect and the vacuum cannot be maintained, and the cells collapse at high temperatures.
[0005] (4) The existing structure has no zoned stepped design and uses the same material in the entire temperature range of 300-750℃. The functions of low-temperature heat absorption, medium-temperature oxygen isolation and high-temperature shell formation cannot be accurately matched, resulting in waste of material performance and insufficient fire resistance limit. For example, Chinese patent CN209980847U discloses a medium-voltage fireproof power cable that uses a combination of mica tape wrapping and ceramicized polyolefin insulation extrusion. However, this structure still uses a single ceramicized layer as the main fire-resistant means and does not have a zoned functional design according to different temperature ranges.
[0006] (5) The proportion of flame retardant fillers is unreasonable. ATH alone has insufficient flame retardancy, and too much MDH results in high processing viscosity and foam breakage. The foaming system lacks foam stabilization and temperature control processes, making it difficult to stabilize the degree of foaming and closed-cell rate. The oxygen index is often below 40, and the low smoke and halogen-free properties do not meet high-end standards. Summary of the Invention
[0007] 1. Purpose of the invention Overcoming the shortcomings of existing fire-resistant cables, such as poor heat insulation due to single-layer structure, cracking of ceramic shell, thermal conductivity of open-cell foam layer, and fire resistance time of <180min, we provide a three-zone stepped fire-resistant composite structure, high oxygen index vacuum closed-cell formula, and matching closed extrusion negative pressure shaping process, which greatly improves the long-term fire resistance reliability of medium-voltage cables.
[0008] 2. Technical Solution To achieve the above objectives, the present invention adopts the following technical solution: Firstly, a highly reliable integrated fire-resistant layer is provided, located between the cable core and the outer sheath, and consists of the following layers from the inside out: an inner wrapping insulation layer (fiberglass tape), a low-temperature zone fire-resistant layer (foamed insulation layer + mineral fire-retardant mortise-and-tenon interlocking interlocking layer), a low-temperature wrapping insulation layer (fiberglass tape), a medium-temperature zone fire-resistant layer (foamed insulation layer + mineral fire-retardant mortise-and-tenon interlocking interlocking layer), a medium-temperature wrapping insulation layer (fiberglass tape), a high-temperature zone fire-resistant layer (foamed insulation layer + ceramicized polyolefin mortise-and-tenon interlocking interlocking layer), a high-temperature wrapping fire-resistant layer (ceramized tape), and an outer wrapping insulation layer (fiberglass tape). The mortise-and-tenon interlocking ... The convex corners of the protruding teeth and the concave corners of the grooves are all chamfered to facilitate the extrusion molding of the insulation layer and avoid stress concentration. The height of the protruding teeth is 80%–120% of the effective thickness of the extruded insulation layer, the width of the grooves is 80%–120% of the width of the protruding teeth, and the width of the protruding teeth is 1.5–3 times the height of the protruding teeth. These dimensional proportions ensure that the toothed interlocking structure has sufficient mechanical interlocking strength, while avoiding extrusion difficulties and interlayer instability caused by excessively high or wide protruding teeth. It is suitable for low-temperature zones (300–450℃), medium-temperature zones (450–600℃), and high-temperature zones (600–750℃). Each zone is physically separated by wrapping tape, forming an independent thermal management unit.
[0009] Furthermore, the inner heat insulation layer, the low-temperature zone heat insulation layer, the medium-temperature zone heat insulation layer, and the outer heat insulation layer are all wrapped with one or more layers of fiberglass tape with an overlap rate of 40% to 60%; the high-temperature zone fireproof layer is wrapped with one or more layers of ceramicized fireproof tape.
[0010] Furthermore, the fireproof layer in the low-temperature and medium-temperature zones is made of mineral fireproof putty; the fireproof layer in the high-temperature zone is made of ceramicized halogen-free, low-smoke, flame-retardant polyolefin material; the extruded insulation layer in each zone is made of foamed halogen-free, low-smoke, flame-retardant polyolefin; the foaming degree of the extruded insulation layer is 25% to 35%, the absolute pressure of the closed-cell internal air pressure is ≤0.03MPa, the closed-cell rate is ≥98%, and the oxygen index is ≥43; the thickness of the extruded insulation layer is 1.5 to 2.5 mm, the thickness of the fireproof layer is 0.3 to 0.8 mm, and the thickness of the high-temperature ceramicized layer is 1.5 to 2.5 mm.
[0011] Secondly, a special formulation for extruded insulation layers in integrated refractory structures is provided. The extruded insulation layer formulation includes, by weight, EVA, LLDPE, POE (ethylene-octene copolymer), MAH (grafted EVA compatibilizer), silane-modified ATH, silane-modified MDH, low-borosilicate glass powder, wollastonite powder, low-temperature AC foaming agent, zinc oxide, silicone foam stabilizer, composite antioxidant, KH550 silane coupling agent, and polyethylene wax; EVA has a VA content of 20%~28%, with an addition amount of 25~40 parts; LLDPE has a melt flow index (MFR) of 1.5~2.5, with an addition amount of 10~25 parts; POE has an addition amount of 5~15 parts; MAH (grafted EVA compatibilizer) has an addition amount of 5~12 parts; and silane-modified ATH has a particle size (D50) of 2.0~3.0 μm, with an addition amount of 90~130 parts. The following components are added: silane-modified MDH with a particle size D50 of 2.3-3.3 μm, 40-70 parts; low borosilicate glass powder, 8-16 parts; wollastonite powder, 5-12 parts; low-temperature AC foaming agent, 2.5-4.0 parts; zinc oxide, 0.5-1.2 parts; organosilicon foam stabilizer, 1.0-2.0 parts; composite antioxidant, 0.3-1.0 parts; KH550 silane coupling agent, 0.8-1.8 parts; polyethylene wax, 1.0-2.5 parts; the composite antioxidant is a mixture of hindered phenolic primary antioxidant 1010 and phosphite secondary antioxidant 168 in a 1:1 mass ratio.
[0012] Preferably, the extruded insulation layer comprises, by weight, 32 parts EVA, 18 parts LLDPE, 10 parts POE ethylene-octene copolymer, 8 parts MAH grafted EVA compatibilizer, 110 parts silane-modified ATH, 55 parts silane-modified MDH, 12 parts low borosilicate glass powder, 8 parts wollastonite powder, 3.2 parts low-temperature AC foaming agent, 0.8 parts zinc oxide, 1.5 parts silicone foam stabilizer, 0.6 parts composite antioxidant, 1.2 parts KH550 silane coupling agent, and 1.8 parts polyethylene wax; the VA content of EVA is 24%, the melt flow index (MFR) of LLDPE is 2.0, the particle size (D50) of silane-modified ATH is 2.5 μm, and the particle size (D50) of silane-modified MDH is 2.8 μm; the mass ratio of ATH to MDH is 2:1, and the total filler content is 165. The total addition of low borosilicate glass powder and wollastonite is 20 parts, ensuring an oxygen index ≥43 and high-temperature ceramic skeleton strength. The foaming agent and foam stabilizer work synergistically to achieve a foaming degree of 25%–35% and a closed-cell internal pressure ≤0.03MPa.
[0013] Thirdly, a granule preparation method for the extruded insulation layer formulation is provided, including filler pretreatment, stepwise premixing, and intensive mixing granulation; the filler and coupling agent are activated at 80°C for 8 min at high speed; the resin, compatibilizer, and pretreated powder are premixed at 60°C at low speed for 3 min and then at high speed for 6 min, with the foaming agent and additives added during the high-speed stage; the intensive mixing temperature is 130–145°C, and the time is 12–15 min, preferably 14 min; the granulation is carried out using a twin-screw extruder at 140–170°C, followed by double-layer filtration, water-cooled pelletizing, and the finished product moisture content is ≤0.05%.
[0014] Fourthly, a method for preparing an extruded heat insulation layer in a composite fire-resistant structure of a power cable is provided, comprising the following steps: the extruded heat insulation layer granules are sieved through an 80-mesh sieve and dried in a sealed environment at 70-75℃ for 2 hours until the moisture content is ≤0.05%; the cable core is dehumidified by hot air at 60℃; the extruder is subjected to segmented temperature control at 155-185℃, with a momentary temperature not exceeding 190℃; a sealed forced feeding system is used, with a low-shear screw speed of 15-25 r / min, preferably 20 r / min, and a melt back pressure of 14-16 MPa, preferably 15 MPa; immediately after extrusion, the material enters a negative pressure shaping die, with an internal die pressure of -0.07 to -0.09 MPa and a locking time of 3-5 seconds, preferably... Select -0.08MPa, lock the hole for 4s, and extract the air inside the bubble to form a vacuum closed cell; then cure it in three stages of sealed water tanks: pre-cooling at 50-55℃, intermediate cooling at 35-40℃, and final cooling at 25℃. The preferred method is three-stage water cooling (pre-cooling at 52℃, intermediate cooling at 38℃, and final cooling at 25℃); online X-ray thickness measurement and AI vision inspection, closed-loop matching of traction speed, finished product foaming degree 30%±5%, closed cell rate ≥98%, layer eccentricity ≤15%, and oxygen index ≥43.
[0015] Furthermore, when the moisture content of the aggregate is >0.05%, the absolute value of the negative pressure of the shaping mold is increased by 0.01~0.02MPa in a linked adjustment; for every 0.01% increase in moisture content, the absolute value of the negative pressure increases by 0.005MPa accordingly; the traction speed is 1.5~3.0m / min, the length of each water tank section is ≥2m, and the cooling time is ensured to be ≥5s. The machine is then cleaned with graded temperature control during shutdown.
[0016] This invention also provides a high-reliability medium-voltage fire-resistant power cable, comprising a cable core, the aforementioned integrated fire-resistant structure, and an outer sheath. The integrated fire-resistant structure is prepared using the aforementioned extruded insulation layer formula and granules, and employs the aforementioned extrusion method for the insulation layer. The cable can still pass a 950℃, 180-minute fire resistance test after a bending radius of 15D, meeting the GB / T 19216 standard. It can be used in fire-fighting power supply circuits for subways, high-rise buildings, or nuclear power plants.
[0017] After the overall cable is assembled, the low-temperature zone dehydrates and absorbs heat, the medium-temperature zone has foam compaction and oxygen isolation, and the high-temperature zone has ceramic shell formation. The triple protection works together to provide fire resistance for ≥180 minutes, and the fire resistance performance does not decrease after bending radius of 15D.
[0018] 3. Beneficial effects Compared with the prior art, the present invention has the following significant advantages: (1) Three-zone stepped heat insulation, the heat transfer path is doubled, the fire resistance time is stable at 180 min, and it passes the 950℃ test; (2) The vacuum closed-cell structure retains water vapor for long-term heat absorption, reduces the thermal conductivity, and eliminates convection loss; (3) ATH / MDH compound synergistic flame retardancy, oxygen index ≥43, combustion generates a continuous and dense ceramic layer, no cracking; (4) Closed extrusion + negative pressure lock hole + gradient water cooling, closed cell rate ≥98%, eccentricity ≤15%, high consistency; (5) The multi-layer wrapping of the fire-resistant layer forms a composite barrier, which significantly improves the reliability of power supply during fires; (6) The fire resistance does not decrease after bending, which meets the requirements of engineering installation.
[0019] (7) This invention is applicable to special power supply and distribution scenarios such as subways, super high-rise buildings, and nuclear power plants that require a fire resistance time of 180 minutes. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the layered structure of the cable cross-section; Markings: 100 Cable core; 200 Composite fire-resistant layer; 210 Inner wrapping insulation layer; 220 Low-temperature zone fire-resistant layer (221 Extruded insulation layer, 222 Mineral fire-resistant layer); 230 Low-temperature wrapping insulation layer; 240 Medium-temperature zone fire-resistant layer (241 Extruded insulation layer, 242 Mineral fire-resistant layer); 250 Medium-temperature wrapping insulation layer; 260 High-temperature zone fire-resistant layer (261 Extruded insulation layer, 262 Ceramicized fire-resistant layer); 270 High-temperature wrapping fire-resistant layer; 280 Outer wrapping insulation layer; 300 Outer sheath; Figure 1For structural illustration, the toothed interlocking is a continuous surface structure extending along the cable axis, with its axial cross-section exhibiting a sawtooth corrugated shape; see the text description for specific details. The illustration clearly shows the eight-layer structure arranged sequentially from the inside out, with each zone's fire-resistant layer being a composite layer, reflecting a stepped zoning design. Detailed Implementation
[0021] Example 1: Preparation of extruded thermal insulation layer granules Weigh out 110 parts by weight of silane-modified ATH, 55 parts by weight of MDH, 12 parts by weight of low borosilicate glass powder, and 8 parts by weight of wollastonite. Add them to a high-speed mixer, add 1.2 parts by weight of KH550, and stir at 80°C for 8 minutes to activate. Then add 32 parts by weight of EVA, 18 parts by weight of LLDPE, 10 parts by weight of POE, and 8 parts by weight of MAH-g-EVA, and stir at low speed at 60°C for 3 minutes. Next, add the activated powder, 0.6 parts by weight of composite antioxidant (hindered phenolic primary antioxidant 1010 and phosphite secondary antioxidant 168 compounded in a 1:1 mass ratio), and 1.8 parts by weight of polyethylene wax, and mix at low speed for 2 minutes. Finally, add 3.2 parts by weight of AC foaming agent, 0.8 parts by weight of zinc oxide, and 1.5 parts by weight of organosilicon foam stabilizer, and mix at high speed for 6 minutes. The discharged material was fed into an internal mixer at a controlled temperature of 138℃ and mixed for 14 minutes. Then it entered a twin-screw extruder at a barrel temperature of 140–170℃ and a die temperature of 170℃. After filtration through an 80 / 120 mesh filter, it was water-cooled, pelletized, and dried to a moisture content of 0.04%. The foaming degree was calculated according to GB / T 6343-2009, "Determination of Apparent Density of Foamed Plastics and Rubber," from the difference between the solid density and the apparent density of the foamed sample. Tests showed an oxygen index of 44.2, a foaming degree of 28%–33%, a closed-cell rate of 98.6%, and a dense ceramic layer without cracks after combustion. XRD analysis was performed after calcining the pellets in a muffle furnace at 950℃ for 30 minutes. The results showed that low-borosilicate glass powder reacted with wollastonite above 700℃ to form calcium borosilicate. The glass phase effectively fills the inorganic pores left by ATH / MDH decomposition, forming a continuous and dense ceramic skeleton. This is the key microscopic mechanism for preventing the ceramic layer from cracking.
[0022] Comparative Example 1 (without POE): POE was removed from the formulation, and LLDPE was increased to 28 parts (to compensate for the total resin content). The remaining components and processes were the same. Results: The mixing torque increased by 38% from the baseline of 4.2 N·m to 5.8 N·m, making discharge difficult; the foam wall strength was insufficient during extrusion foaming, the closed-cell rate dropped to 91%, the foaming degree was uneven (22%–38%), and the oxygen index was 41.5.
[0023] Comparative Example 2 (without negative pressure molding): Using the same formula and extrusion parameters, but directly entering room temperature water cooling after extrusion without passing through a negative pressure mold. The closed-cell rate of the finished product is only 82%, the air pressure inside the cells is close to atmospheric pressure, the thermal conductivity is increased, and the 950℃ fire resistance test can only be maintained for 132 minutes.
[0024] Example 2: Assembly of Integrated Refractory Layer Using an 8.7 / 15kV cable core as the base material, from the inside out: ① two layers of fiberglass tape (50% overlap) are wrapped to form an inner wrapping insulation layer 210; ② granules from Example 1 (2.0mm thick) are extruded to form 221, and then mineral fireproof putty (0.5mm thick) is extruded to form 222. The two are pressed and embedded by the trapezoidal protrusions on the outer surface of the extruded insulation layer and the grooves on the inner surface of the fireproof putty, forming a toothed interlocking structure. The height of the protrusions is 100% of the effective thickness of the insulation layer (i.e., 2.0mm), the width of the groove is equal to the width of the protrusions (100%), and the width of the protrusions is twice the height of the protrusions (4.0mm). The top of the protrusions and the concave corners of the grooves are chamfered. The chamfer radius is 0.2-0.3mm, forming the low-temperature zone refractory layer 220 (300-450℃); ③ Wrap two layers of fiberglass tape 230; ④ Repeat the structure ② (same formula foam layer + fireproof putty) to form the medium-temperature zone refractory layer 240 (450-600℃); ⑤ Wrap two layers of fiberglass tape 250; ⑥ Extruded foam layer 261 (thickness 2.0mm) + extruded ceramicized halogen-free polyolefin 262 (thickness 2.0mm) to form the high-temperature zone refractory layer 260 (600-750℃); ⑦ Wrap two layers of ceramicized fireproof tape 270; ⑧ Wrap multiple layers of fiberglass tape 280 as the outermost layer of insulation to isolate external open flame radiation; finally, extruded outer sheath 300.
[0025] Example 3: Extrusion preparation process of extruded thermal insulation layer The granules are sieved through an 80-mesh screen, dried in a sealed hot air chamber at 72℃ for 2 hours, and then left to stand in a sealed environment for 30 minutes before being pneumatically conveyed to the hopper. The cable core is dehumidified with hot air at 60℃. The SJ150 extruder is heated as follows: feeding section 158℃, compression section 162℃, homogenization section 172℃, and die head 182℃, and held at these temperatures for 30 minutes. The water ring vacuum pump is set to -0.08MPa, and the negative pressure fluctuation of the die sealing ring is ±0.008MPa. The temperatures of the three water tank sections are set to 52℃, 38℃, and 25℃, respectively. The screw speed is 20 r / min, the melt back pressure is 15MPa, and after extrusion from the die head, the material enters the die locking hole for 4 seconds, then passes through the three water tank sections in sequence, each section being 2.5m long, with a traction speed of 2.0m / min. The molding mold features a double-layer water-cooled jacket structure with three rows of Φ0.3mm micropores evenly distributed axially on the inner wall, each row containing 12 pores, communicating with the vacuum chamber. The mold cavity is 600mm long, with fluororubber sealing rings at both ends to prevent backflow of external air. Online X-ray thickness measurement shows an eccentricity of 13.2%, and AI vision shows no defects. The finished product has a foaming degree of 29.7%, a closed-cell rate of 98.5%, and an oxygen index of 44.1.
[0026] When the moisture content of the aggregate unexpectedly rises to 0.06% (simulated anomaly), the system automatically adjusts the negative pressure to -0.095MPa, and the closed-cell rate of the finished product still reaches 97.8%, proving that the linkage adjustment is effective.
[0027] Example 4: Verification of fire resistance after bending The cable of this invention was bent to a diameter of 15D and then subjected to a flame resistance test at 950℃ according to GB / T 19216. The rated phase voltage U0 (8.7kV, i.e., the rated phase voltage of the cable) was continuously applied for 180 minutes. The cable core insulation did not break down, and the insulation resistance decreased by no more than 8% from the initial value. This is compared to a single-layer mica tape cable (which broke down after 85 minutes of fire resistance after bending) and a conventional single-layer ceramicized cable (which broke down after 110 minutes of bending). After combustion, the flame of this invention was removed, and the fire-resistant layer formed a complete ceramic shell without penetrating cracks. The smoke density and light transmittance were ≥60%, and the halogen acid gas release was ≤0.5mg / g. These results demonstrate that the cable of this invention fully meets the stringent requirements for fire resistance time and low smoke and halogen-free operation in special applications such as subways, high-rise buildings, and nuclear power plants.
[0028] Example 5: Shutdown Maintenance Process Short-term shutdown (≤20min): Screw idle speed 5r / min, die head temperature drop 8℃, vacuum pump maintain -0.02MPa to prevent moisture backflow. Long-term shutdown (>40min): Introduce PE cleaning material to purge the foaming melt, cool in sections to below 80℃, disassemble the die head, and clean the carbonized residue; before restarting, repeat the heating program, negative pressure calibration, and flow calibration process.
[0029] Summary of Formulas and Process Parameters The composition includes: 25-40 parts EVA, 10-25 parts LLDPE, 5-15 parts POE, 5-12 parts MAH-g-EVA, 90-130 parts ATH, 40-70 parts MDH, 8-16 parts glass powder, 5-12 parts wollastonite, 2.5-4.0 parts AC foaming agent, and 1.0-2.0 parts foam stabilizer (preferred values from Example 1). The composite antioxidant is a mixture of hindered phenolic primary antioxidant 1010 and phosphite secondary antioxidant 168 in a 1:1 mass ratio.
[0030] ATH / MDH = 2:1, total filler 165 parts; glass powder + wollastonite = 20 parts (according to preferred embodiment 1).
[0031] The mixing temperature is 138℃, and the maximum temperature for twin-screw extruders is 170℃.
[0032] The extruder has a temperature range of 155–185℃, a back pressure of 15MPa, and a screw speed of 20r / min.
[0033] Negative pressure -0.08MPa, lock hole 4s.
[0034] Water-cooled three-stage system at 52 / 38 / 25℃, traction speed 2.0m / min.
[0035] Finished product: foaming degree 30%±5%, closed cell rate ≥98%, eccentricity ≤15%, oxygen index ≥43.
[0036] All embodiments demonstrate that the three-zone stepped vacuum closed-cell structure and supporting process of the present invention can stably achieve 950℃ and 180min fire resistance, and the performance does not decrease after bending, fully meeting the requirements of high-end engineering.
[0037] The above provides a detailed description of a high-reliability medium-voltage fire-resistant power cable and its supporting integrated fire-resistant structure, insulation layer formula, and preparation method provided by embodiments of the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. It should be understood that the above embodiments are only for illustrating the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, or combinations made within the spirit and principles of the present invention should be included within the scope of protection of the present invention. In summary, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A high-reliability, medium-voltage fire-resistant power cable integrated fire-resistant structure, characterized in that: Located between the cable core and the outer sheath, the structure, from the inside out, comprises an inner heat-insulating layer, a low-temperature fire-resistant layer, a low-temperature heat-insulating layer, a medium-temperature fire-resistant layer, a medium-temperature heat-insulating layer, a high-temperature fire-resistant layer, a high-temperature fire-resistant layer, and an outer heat-insulating layer. The low-temperature fire-resistant layer is suitable for temperatures of 300–450℃, the medium-temperature layer for 450–600℃, and the high-temperature layer for 600–750℃. Each fire-resistant layer is composed of an extruded heat-insulating layer and a fire-resistant layer that are radially toothed, interlocked, and cross-composite. Furthermore, adjacent layers are physically separated by a wrapping insulation layer; the toothed interlocking refers to the circumferential distribution of trapezoidal protrusions on the outer surface of the extruded insulation layer, and the opening of matching trapezoidal grooves on the inner surface of the fireproof layer. After the two are pressed together, the protrusions are embedded in the grooves to form a radial interlock. The protrusions at the top of the protrusions and the concave corners of the grooves are all chamfered. The height of the protrusions is 80% to 120% of the effective thickness of the extruded insulation layer, the width of the groove is 80% to 120% of the width of the protrusions, and the width of the protrusions is 1.5 to 3 times the height of the protrusions. Its axial cross-section has continuous sawtooth-shaped corrugations.
2. The high-reliability medium-voltage fire-resistant power cable integrated fire-resistant structure according to claim 1, characterized in that: The inner heat insulation layer, the low-temperature zone heat insulation layer, the medium-temperature zone heat insulation layer, and the outer heat insulation layer are all wrapped with one or more layers of fiberglass tape with an overlap rate of 40% to 60%; the high-temperature zone fireproof layer is wrapped with one or more layers of ceramicized fireproof tape.
3. The high-reliability medium-voltage fire-resistant power cable integrated fire-resistant structure according to claim 1, characterized in that: The fireproof layer in the low-temperature and medium-temperature zones is made of mineral fireproof putty; the fireproof layer in the high-temperature zone is made of ceramicized halogen-free, low-smoke, flame-retardant polyolefin material; the extruded insulation layer in each zone is made of foamed halogen-free, low-smoke, flame-retardant polyolefin; the foaming degree of the extruded insulation layer is 25% to 35%, the absolute pressure of the closed-cell internal air pressure is ≤0.03MPa, the closed-cell rate is ≥98%, and the oxygen index is ≥43; the thickness of the extruded insulation layer is 1.5 to 2.5 mm, the thickness of the fireproof layer is 0.3 to 0.8 mm, and the thickness of the high-temperature ceramicized layer is 1.5 to 2.5 mm.
4. A formulation for an extruded insulation layer used in the integrated fire-resistant structure of a high-reliability medium-voltage fire-resistant power cable as described in any one of claims 1 to 3, characterized in that: The extruded insulation layer formulation includes, by weight, EVA, LLDPE, POE ethylene-octene copolymer, MAH grafted EVA compatibilizer, silane-modified ATH, silane-modified MDH, low borosilicate glass powder, wollastonite powder, low-temperature AC foaming agent, zinc oxide, silicone foam stabilizer, composite antioxidant, KH550 silane coupling agent, and polyethylene wax; EVA has a VA content of 20%~28%, with an addition amount of 25~40 parts; LLDPE has a melt flow index (MFR) of 1.5~2.5, with an addition amount of 10~25 parts; POE ethylene-octene copolymer has an addition amount of 5~15 parts; MAH grafted EVA compatibilizer has an addition amount of 5~12 parts; silane-modified ATH has a particle size (D50) of 2.0~3.0μm, with an addition amount of 90~130 parts; silane-modified MDH... The particle size D50 is 2.3~3.3μm, and the addition amount is 40~70 parts; the addition amount of low borosilicate glass powder is 8~16 parts; the addition amount of wollastonite powder is 5~12 parts; the addition amount of low temperature AC foaming agent is 2.5~4.0 parts; the addition amount of zinc oxide is 0.5~1.2 parts; the addition amount of organosilicon foam stabilizer is 1.0~2.0 parts; the addition amount of composite antioxidant is 0.3~1.0 parts; the addition amount of KH550 silane coupling agent is 0.8~1.8 parts; the addition amount of polyethylene wax is 1.0~2.5 parts; the composite antioxidant is a mixture of hindered phenolic main antioxidant 1010 and phosphite auxiliary antioxidant 168 in a mass ratio of 1:
1.
5. The extruded thermal insulation layer formulation according to claim 4, characterized in that: The extruded insulation layer comprises, by weight, 32 parts EVA, 18 parts LLDPE, 10 parts POE ethylene-octene copolymer, 8 parts MAH grafted EVA compatibilizer, 110 parts silane-modified ATH, 55 parts silane-modified MDH, 12 parts low borosilicate glass powder, 8 parts wollastonite powder, 3.2 parts low-temperature AC foaming agent, 0.8 parts zinc oxide, 1.5 parts organosilicon foam stabilizer, 0.6 parts composite antioxidant, 1.2 parts KH550 silane coupling agent, and 1.8 parts polyethylene wax; the VA content of EVA is 24%, the melt flow index (MFR) of LLDPE is 2.0, the particle size (D50) of silane-modified ATH is 2.5 μm, and the particle size (D50) of silane-modified MDH is 2.8 μm; the mass ratio of ATH to MDH is 2:1, and the total filler content is 165. The total amount of low borosilicate glass powder and wollastonite added is 20 parts.
6. A method for preparing granules for use in the extrusion insulation layer formulation of claim 4 or 5, characterized in that: The process includes filler pretreatment, stepwise premixing, and intensive mixing and granulation; the filler and KH550 coupling agent are activated at 80℃ for 8 minutes at high speed; the resin, compatibilizer, and pretreated powder are premixed at 60℃ at low speed for 3 minutes and then at high speed for 6 minutes, with the foaming agent and additives added during the high-speed stage; the intensive mixing temperature is 130-145℃ and the time is 12-15 minutes; the twin-screw granulation temperature is 140-170℃, filtered through an 80 / 120 mesh double-layer filter, water-cooled and pelletized, and the finished product has a moisture content of ≤0.05% and is stored in a sealed container.
7. A method for extruding and preparing an extruded heat insulation layer in a composite fire-resistant structure for power cables, characterized in that, Includes the following steps: The extruded insulation layer granules are sieved through an 80-mesh screen and dried in a sealed environment at 70-75℃ for 2 hours until the moisture content is ≤0.05%. The cable core is dehumidified with hot air at 60℃. The extruder is temperature-controlled in stages at 155-185℃, with a momentary temperature not exceeding 190℃. The extruder uses a sealed forced feeding system with a low-shear screw speed of 15-25 r / min and a melt back pressure of 14-16 MPa. After extrusion, the material immediately enters a negative pressure shaping mold with an internal pressure of -0.07 to -0.09 MPa and a locking time of 3-5 seconds. Subsequently, the material is cured in a sealed water tank in three stages: pre-cooling at 50-55℃, intermediate cooling at 35-40℃, and final cooling at 25℃. The finished product has a foaming degree of 30%±5%, a closed-cell rate of ≥98%, a layer eccentricity of ≤15%, and an oxygen index of ≥43.
8. The extrusion preparation method of the extruded heat insulation layer according to claim 7, characterized in that: When the moisture content of the granules is >0.05%, the absolute value of the negative pressure of the shaping mold will be increased by 0.01 to 0.02 MPa; for every 0.01% increase in moisture content, the absolute value of the negative pressure will be increased by 0.005 MPa; the traction speed will be 1.5 to 3.0 m / min, the length of each water tank section will be ≥2 m, and the cooling time will be ≥5 s.
9. A high-reliability medium-voltage fire-resistant power cable, characterized in that: The cable comprises a cable core, an integrated fire-resistant structure as described in any one of claims 1 to 3, and an outer sheath. The integrated fire-resistant structure adopts the extruded insulation layer formulation as described in claims 4 and 5 and the granules prepared as described in claim 6, and adopts the extrusion preparation method of the extruded insulation layer as described in claim 7 or 8. The cable can still pass the fire resistance test at 950°C for 180 minutes after bending a radius of 15D, meeting the GB / T 19216 standard.
10. A high-reliability medium-voltage fire-resistant power cable according to claim 9, characterized in that: The cable is used for fire protection power supply circuits in subways, high-rise buildings, or nuclear power plants.
Citation Information
Patent Citations
Medium-voltage fireproof power cable
CN209980847U
High-flame-retardant fireproof variable frequency cable
CN221946844U